2020
DOI: 10.1016/j.annonc.2020.08.1824
|View full text |Cite
|
Sign up to set email alerts
|

1760P COVID-19 severe pneumonia in cancer patients: Impact and predictive factors

Abstract: Background: Representatives from 8 global cancer coalitions/alliances, representing 650 cancer patient groups and the interests of over 14 million patients have come together during the pandemic to review and evaluate the patient-perspective impact. Cancer services have faced challenges as a result of COVID-19, including suspension of screening and diagnostic services; delays in diagnosis leading to higher mortality rates; cancellation/deferral of life-saving treatments; changes in treatment regimens and suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…We calculated that the presence of such symptoms on admission doubles the risk of death in our cancer patients, and the generated curve shows a lower survival chance in this COVID-19 patient group (Figure 3). The literature confirms that severe pneumonia is frequent in cancer patients with COVID-19 and leads to high mortality [26]. Although rales are considered the most common symptom at chest auscultation in COVID-19 patients [27] and were identified in 26 oncology patients (Table S2), they were not a variable affecting the risk of death (p = 0.709).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…We calculated that the presence of such symptoms on admission doubles the risk of death in our cancer patients, and the generated curve shows a lower survival chance in this COVID-19 patient group (Figure 3). The literature confirms that severe pneumonia is frequent in cancer patients with COVID-19 and leads to high mortality [26]. Although rales are considered the most common symptom at chest auscultation in COVID-19 patients [27] and were identified in 26 oncology patients (Table S2), they were not a variable affecting the risk of death (p = 0.709).…”
Section: Discussionmentioning
confidence: 79%
“…Although rales are considered the most common symptom at chest auscultation in COVID-19 patients [27] and were identified in 26 oncology patients (Table S2), they were not a variable affecting the risk of death (p = 0.709). Lung tumors are considered a risk factor for developing this condition [26]. A recent updated study of survival in patients with COVID-19 disease and lung cancer, which included more than 21,000 patients, found that lung cancer modifies COVID-19 prognosis in terms of disease progression and mortality [28].…”
Section: Discussionmentioning
confidence: 99%